2013
DOI: 10.1007/s12011-013-9768-7
|View full text |Cite
|
Sign up to set email alerts
|

Individual Intake of Free-Choice Mineral Mix by Grazing Beef Cows May Be Less Than Typical Formulation Assumptions and Form of Selenium in Mineral Mix Affects Blood Se Concentrations of Cows and Their Suckling Calves

Abstract: The objectives of this study were to determine (1) the individual ad libitum intake of mineral mix by beef cows managed under a year-long, fall-calving, forage-based production regimen and (2) if Se form in the mineral mix affected the blood Se concentrations of cows and suckling calves. Twenty-four late-gestation (6 to 8 months) Angus-cross cows (2.7 ± 0.8 years; body weight [BW] = 585 ± 58 kg) were blocked by BW and randomly assigned (n = 8) to a mineral supplement treatment (TRT) containing 35 ppm Se as eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 31 publications
1
22
1
Order By: Relevance
“…Simultaneously, the Se concentration in the serum of calves born to cows fed with Se-enriched yeast was 1.3-fold higher in comparison with that found in calves born to cows that received inorganic salts. The efficiency of Se transfer across the placenta found in this research is lower than that estimated previously in cattle as a correlation of Se concentrations between fetus-dam in liver (r = 0.65; Gooneratne and Christensen 1989) and in whole doi: 10.17221/86/2016-CJAS blood (r = 0.63; Patterson et al 2013). It may be assumed that the main reason for the higher value of this relationship presented in the cited studies was the comparison of Se concentration in the liver and in the whole blood.…”
Section: Diet-cow Se Transfer Efficiencycontrasting
confidence: 86%
See 1 more Smart Citation
“…Simultaneously, the Se concentration in the serum of calves born to cows fed with Se-enriched yeast was 1.3-fold higher in comparison with that found in calves born to cows that received inorganic salts. The efficiency of Se transfer across the placenta found in this research is lower than that estimated previously in cattle as a correlation of Se concentrations between fetus-dam in liver (r = 0.65; Gooneratne and Christensen 1989) and in whole doi: 10.17221/86/2016-CJAS blood (r = 0.63; Patterson et al 2013). It may be assumed that the main reason for the higher value of this relationship presented in the cited studies was the comparison of Se concentration in the liver and in the whole blood.…”
Section: Diet-cow Se Transfer Efficiencycontrasting
confidence: 86%
“…The maternal supplementation of Se increased Se reserves in the liver of the newborn to meet the Se needs for the normal growth and health (Abdelrahman and Kincaid 1995). The whole blood Se concentrations did not significantly decline even when mineral intake began to decline, and this indicator reflects more chronic or "historical" Se status, whereas serum Se concentration reflects more recent changes in Se nutrition (Stowe and Herdt 1992;Patterson et al 2013). According to the indicators presented in the work cited earlier, the Se concentration in blood serum is more reflective than the concentration in liver or whole blood and may be a more adequate indicator of the nutritional status of Se.…”
Section: Diet-cow Se Transfer Efficiencymentioning
confidence: 99%
“…Supplementing diets with inorganic (ISe, sodium selenite) versus organic (OSe; SelPlex®) forms of Se effects bioavailability (concentrations of Se in blood and tissues) and bioactivity (blood GPx activity) [23][24][25]. In addition, we have demonstrated that the feeding of a 1:1 mix of inorganic and organic forms results in an equal assimilation of Se into blood [24,26] and liver [24] tissues as yielded by feeding only an organic form and that Seadequate cattle consuming equimolar amounts of Se in organic, inorganic, or mixed forms results in distinct liver transcriptome profiles [27]. With regard to the potential that the organic Se supplementation effect was due to the non-methyl Se portion of SeMet, research with mice has shown that equimolar supplementation of methionine versus SeMet results in differential hepatic transcriptome profiles [28,29].…”
Section: Introductionmentioning
confidence: 91%
“…As noted above, the objective of the current report was to determine if the pattern and relative amount of fertility-associated mRNAs expressed by the testis of calves was affected by the form of Se in free-choice mineral-vitamin mixes consumed by dams throughout gestation. The results of the first year (periods 1-13) of that trial have been published [26], whereas the data reported in this manuscript refer to calves born during periods 14-17, the beginning of year 2 of the trial.…”
Section: Animals and Experimental Conditionsmentioning
confidence: 99%
“…This is the equivalent of 120 parts per million (ppm) of Se added to a salt supplement mixture that is formulated for consumption of one ounce per head per day. The use of free-choice salt-mineral mixes as a method of Se supplementation has limited research, but in some cases has been found to bring Se to adequate levels (Patterson et al 2013). Results can be variable due to individual animal intake, varying pasture conditions and climatic conditions such as temperature, precipitation and season.…”
mentioning
confidence: 99%